Pre-cART elevation of CRP and CD4+ t-cell immune activation associated with HIV clinical progression in a multinational case-cohort study - Ashwin Balagopal (2018)
Copyright © 2015 Wolters Kluwer Health, Inc. All rights reserved. Background: Despite the success of combination antiretroviral therapy (cART), a subset of HIV-infected patients who initiate cART develop early clinical progression to AIDS; therefore, some cART initiators are not fully benefitted by cART. Immune activation precART may predict clinical progression in cART initiators. Methods: A case-cohort study (n = 470) within the multinational Prospective Evaluation of Antiretrovirals in Resource-Limited Settings clinical trial (1571 HIV treatment-naive adults who initiated cART; CD4 < sup > + < /sup > T-cell count ,300 cells/mm3; 9 countries) was conducted. A subcohort of 30 participants per country was randomly selected; additional cases were added from the main cohort. Cases [n = 236 (random subcohort 36; main cohort 200)] had clinical progression (incident WHO stage 3/4 event or death) within 96 weeks after cART initiation. Immune activation biomarkers were quantified pre-cART. Associations between biomarkers and clinical progression were examined using weighted multivariable Cox-proportional hazards models. Results: Median age was 35 years, 45% were women, 49% black, 31% Asian, and 9% white. Median CD4 < sup > + < /sup > T-cell count was 167 cells per cubic millimeter. In multivariate analysis, highest quartile C-reactive protein concentration [adjusted hazard ratio (aHR), 2.53; 95% confidence interval (CI): 1.02 to 6.28] and CD4+ T-cell activation (aHR, 5.18; 95% CI: 1.09 to 24.47) were associated with primary outcomes, compared with lowest quartiles. sCD14 had a trend toward association with clinical failure (aHR, 2.24; 95% CI: 0.96 to 5.21). Conclusions: Measuring C-reactive protein and CD4 < sup > + < /sup > T-cell activation may identify patients with CD4 < sup > + < /sup > T-cell counts ,300 cells per cubic millimeter at risk for early clinical progression when initiating cART. Additional vigilance and symptom-based screening may be required in this subset of patients even after beginning cART.